Research Advance on Qingfei Paidu Decoction in Prescription Principle, Mechanism Analysis and Clinical Application - Ren, Wei; Ma, Yue; Wang, Raoqiong; Liang, Pan; Sun, Qin; Pu, Qingrong; Dong, Li; Mazhar, Maryam; Luo, Gang; Yang, Sijin (Frontiers in Pharmacology, 2021)
Since the sudden epidemic of coronavirus disease 2019 , the State Administration of Traditional Chinese Medicine immediately organized experts to formulate and screen the effective prescriptions of traditional Chinese medicine according to the characteristics of the novel coronavirus infection. Qingfei Paidu decoction ( QFPDD) has been proven to be effective in multi-provincial clinical trials, and has been selected as a general prescription for the treatment of COVID-19 in different stages that was later promoted to be used nationwide. This review highlights the latest advances of QFPDD, focusing on the TCM theory, mechanism analysis, clinical application of QFPDD and its future perspectives. Moreover, an in-depth discussion of some valuable issues and possible development for future research on QFPDD is also discussed, aiming to provide a novel guide to combat the global epidemic COVID-19.